2006
DOI: 10.1086/507014
|View full text |Cite
|
Sign up to set email alerts
|

CO(1–0) inz≳ 4 Quasar Host Galaxies: No Evidence for Extended Molecular Gas Reservoirs

Abstract: We present 12 CO(J=1→0) observations of the high-redshift quasi-stellar objects (QSOs) BR 1202-0725 (z = 4.69), PSS J2322+1944 (z = 4.12), and APM 08279+5255 (z = 3.91) using the NRAO Green Bank Telescope (GBT) and the MPIfR Effelsberg 100 m telescope. We detect, for the first time, the CO ground-level transition in BR 1202-0725. For PSS J2322+1944 and APM 08279+5255, our observations result in line fluxes that are consistent with previous NRAO Very Large Array (VLA) observations, but they reveal the full line… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

38
231
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 173 publications
(269 citation statements)
references
References 52 publications
38
231
0
Order By: Relevance
“…, is (5.7 ± 1.0) × 10 10 K km s −1 pc −2 in SW022550, and (8.3 ± 1.2) × 10 10 K km s −1 pc −2 in SW022513 (see Solomon et al 1997, and Assuming an L CO(1−0) /L CO(4−3) ratio equal to unity, as observed in high-z type I QSOs (Riechers et al 2006;Weiß et al 2007) 4 , the total H 2 + He molecular gas mass can be estimated as M gas = M(H 2 + He) = α L CO(1−0) , where α is the CO luminosity to gas mass conversion factor. We adopt α = 0.8 M (K km s −1 pc 2 ) −1 , which has been estimated from local ultraluminous infrared galaxies (ULIRGs; Solomon et al 1997;Downes & Solomon 1998), and is commonly adopted for highredshift ULIRGs (Solomon & Vanden Bout 2005;Tacconi et al 2008;Bothwell et al 2010;Yan et al 2010).…”
Section: Co Line Intensitymentioning
confidence: 67%
“…, is (5.7 ± 1.0) × 10 10 K km s −1 pc −2 in SW022550, and (8.3 ± 1.2) × 10 10 K km s −1 pc −2 in SW022513 (see Solomon et al 1997, and Assuming an L CO(1−0) /L CO(4−3) ratio equal to unity, as observed in high-z type I QSOs (Riechers et al 2006;Weiß et al 2007) 4 , the total H 2 + He molecular gas mass can be estimated as M gas = M(H 2 + He) = α L CO(1−0) , where α is the CO luminosity to gas mass conversion factor. We adopt α = 0.8 M (K km s −1 pc 2 ) −1 , which has been estimated from local ultraluminous infrared galaxies (ULIRGs; Solomon et al 1997;Downes & Solomon 1998), and is commonly adopted for highredshift ULIRGs (Solomon & Vanden Bout 2005;Tacconi et al 2008;Bothwell et al 2010;Yan et al 2010).…”
Section: Co Line Intensitymentioning
confidence: 67%
“…To further constrain the 12 CO/ 13 CO abundance ratio of the Cloverleaf QSO, Table 2 provides flux densities and brightness temperatures of seven 12 CO transitions. To simulate these values, a Large Velocity gradient (LVG) model was used with collision rates from Flower (2001), a cosmic microwave background of 9.7 K, and an ortho-to-para H 2 abundance ratio of three (e.g., Weiß et al 2005Weiß et al , 2007Riechers et al 2006b). The latter is, however, not critical for this study.…”
Section: Large Velocity Gradient Model Calculationsmentioning
confidence: 99%
“…Bradford et al (2009) suggest that in the Cloverleaf the velocity dispersion may exceed the virial requirement by at least an order of magnitude. Therefore the best choice may be [ 12 CO]/([H 2 ](dv/dr)) = 10 −6...−5 pc (km s −1 ) −1 (for the higher value see, e.g., Riechers et al 2006b;Weiß et al 2007) to simultaneously fit the observed CO transitions from J = 1 → 0 up to 11 → 10. Depending on the adopted kinetic temperature (30-50 K) and cloud morphology, and irrespective of the optimal [ 12 CO]/([H 2 ](dv/dr)) value (as long as it is in the wide range displayed by Figs.…”
Section: Large Velocity Gradient Model Calculationsmentioning
confidence: 99%
“…The relatively recent availability of Ka-band receivers on the Karl G. Jansky Very Large Array (VLA) and the Robert C. Byrd Green Bank Telescope (GBT) has led to a small but growing number of CO detections inz 2-3 galaxies that are complete down to the lowest rotational line, CO(1-0), which is crucial for tracing the coldest gas components (e.g., Harris et al 2010Harris et al , 2012Swinbank et al 2010;Danielson et al 2011;Ivison et al 2011Ivison et al , 2012Ivison et al , 2013Riechers et al 2011bRiechers et al , 2011cRiechers et al , 2011dThomson et al 2012Thomson et al , 2015Fu et al 2013;Sharon et al 2013Sharon et al , 2015; for CO(1-0) detections at other redshifts using other bands, see Carilli et al 2002;Greve et al 2003;Hainline et al 2006;Riechers et al 2006Riechers et al , 2009Riechers et al , 2011dRiechers et al , 2013Dannerbauer et al 2009;Aravena et al 2010Aravena et al , 2014Aravena et al , 2016Carilli et al 2010;Emonts et al 2011). , indicative of a multiphase molecular ISM including a previously unaccounted for cold gas reservoir (e.g., Harris et al 2010;Swinbank et al 2010;Danielson et al 2011;Ivison et al 2011;Thomson et al 2012;Bothwell et al 2013; see Riechers et al 2011c;Sharon et al 2013Sharon et al , 2015.…”
Section: Introductionmentioning
confidence: 99%